Penerapan Technology Acceptance Model (TAM) Pada Sistem Informasi Akademik (SIA) Universitas Muhammadiyah Gorontalo - Hasyim, Wahyudin; Biya, Indrawati (SPECTA Journal of Technology, 2024)
This study aims to examine user satisfaction through the application of technology acceptance models in academic information systems. The population of this study is active students who use academic information systems as many as 2,282. The technique used in determining the sample size of a population is using the slovin technique. The sample in this study was 500 samples. The analysis technique used is quantitative analysis. The results of this study indicate  The perceived usefulness variable has a significant value of 0.054 > 0.05, so it can be concluded that the hypothesis is rejected. 2) Variable Perceived Ease of use (ease of use) obtained a significant value of 0.000 <0.05, it can be concluded that the hypothesis is accepted. 3) Variable Attitude Toward Using Technology (attitude) obtained a significant value of 0.000 <0.05, it can be concluded that the hypothesis is accepted. 4) Behavioral Intention to Use (intention) variable obtained a significant value of 0.220 > 0.05, so it can be concluded that the hypothesis is rejected.